Identification of Anticryptococcal Bornyl Compounds from Verbesina turbacensis and Their Structure-Activity Relationships - Powers, Chelsea N.; Mayo, John A.; Moriarity, Debra M.; Vogler, Bernhard; Setzer, William N.; McFeeters, Robert L. (Planta Medica, 2022)
Cryptococcus neoformans is an opportunistic fungal pathogen that has limited treatment options. Natural product plant extracts offer a cost-effective option for the discovery of new anticryptococcal lead compounds. The acetone bark extract of Verbesina turbacensis was found to potently inhibit C. neoformans and was subjected to bioautography. Two compounds that inhibited the growth of C. neoformans were isolated and displayed minimum inhibitory concentration values of 10 and 310 µg/mL. The compounds were identified as the bornyl hydroxycinnamic esters bornyl caffeate and bornyl ferulate, respectively. To better understand initial structure-activity relationships, anticryptococcal activity was characterized for similar compounds. All compounds were further evaluated for mammalian cell toxicity using the MTT assay with MCF-7 and HEK-293 cell lines. Overall, bornyl caffeate demonstrated promising anticryptococcal potential given its potent inhibition of C. neoformans and low mammalian cell toxicity.
Keywords: antifungal; Cryptococcus neoformans; natural product extract; bioautography; antifungal drug discovery; bornyl caffeate; Verbesina turbacensis; Asteraceae; Tremellaceae